2006
DOI: 10.1016/j.ydbio.2005.12.053
|View full text |Cite
|
Sign up to set email alerts
|

Conserved regulatory elements establish the dynamic expression of Rpx/HesxI in early vertebrate development

Abstract: TheRpx/Hesx1 homeobox gene is expressed during gastrulation in the anterior visceral and definitive endoderm and the cephalic neural plate. At later stages of development, its expression is restricted to Rathke's pouch, the primordium of the pituitary gland. This expression pattern suggests the presence of at least two distinct regulatory regions that control early and late Rpx transcription. Using transgenic mice, we have demonstrated that regulatory sequences in the 5' upstream region of Rpx are important fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…LHX1 binds the dTAAT and pTAAT elements (referred to hereafter as the dp region) of the Hesx1 locus (Fig. 5D) (Chou et al, 2006). As expected, ChIP-PCR in P19 cells using the anti-HA antibody and the LHX1-HA expression constructs confirmed the binding of LHX1 to the dp region of the Hesx1 locus (Fig.…”
Section: Loss Of Lhx1 Disrupts the Formation Of Anterior Midline Tissuessupporting
confidence: 78%
See 1 more Smart Citation
“…LHX1 binds the dTAAT and pTAAT elements (referred to hereafter as the dp region) of the Hesx1 locus (Fig. 5D) (Chou et al, 2006). As expected, ChIP-PCR in P19 cells using the anti-HA antibody and the LHX1-HA expression constructs confirmed the binding of LHX1 to the dp region of the Hesx1 locus (Fig.…”
Section: Loss Of Lhx1 Disrupts the Formation Of Anterior Midline Tissuessupporting
confidence: 78%
“…Loss of Lhx1 in the AME results in the downregulation of genes that encode WNT signalling antagonists, such as Dkk1, Hesx1, Cer1 and Gsc. Hesx1 is a direct target of LHX1 (Chou et al, 2006) and Hesx1…”
Section: Discussionmentioning
confidence: 99%
“…S7 in the supplementary material). It has also been reported that Lhx1 and Lhx3 activate the Hesx/Rpx/Xanf gene through their common enhancers in mice and Xenopus (Chou et al, 2006). Thus, Lhx3 could function in the organizer, similar to Lhx1.…”
Section: An Evolutionary Scenario For the Gastrula Organizermentioning
confidence: 93%
“…2) was antigen VE-1 (Rosenquist and Martin, 1995), providing clues that the EVE is molecularly regionalized. Then, a number of gene products, mainly transcription factors that are also found in other tissues, such as the node and/or anterior neural plate, started to be found in both chick primary hypoblast and mouse EVE, including the homeobox genes Otx2 (Acampora et al, 2009;Albazerchi et al, 2007;Bally-Cuif et al, 1995;Kurokawa et al, 2010;PereaGomez et al, 2001), Hex (Yatskievych et al, 1999) and Hesx1/Rpx (Chou et al, 2006;Thomas and Beddington, 1996), and others encoding transcription factors of the GATA and SOX families (Artus et al, 2011).…”
Section: Gene Expression In the Hypoblast And Vementioning
confidence: 99%